Carbonic anhydrase IV on brain capillary endothelial cells: a marker associated with the blood-brain barrier. - Ghandour, M S (1992)
Carbonic anhydrase (CA) activity plays an important role in controlling cerebrospinal fluid production and also influences neuroexcitation and susceptibility to seizures. Until recently, CA II was the only CA demonstrated in brain. Its distribution is limited to the epithelial cells of the choroid plexus and to the myelin-forming cells, the oligodendrocytes. In this report, we present immunoblots, using an antibody raised to CA IV from rat lung, that show that CA IV is also present in rat and mouse brain. Results of immunohistochemistry and immunoelectron microscopy on sections from rat and mouse brain are presented that show the distribution of CA IV to be quite distinct from that of CA II. CA IV is expressed on and is limited to the luminal surface of endothelial cells of cerebral capillaries. These results establish CA IV as a cytochemical marker associated with the blood-brain barrier and suggest an important role for CA IV in CO2 and HCO3- homeostasis in brain.